The cement of civil society studying networks in localities - Diani, Mario 1957- (Cambridge Univ. Press, 2015)
Civil society is frequently conceived as a field of multiple organizations, committed to highly diverse causes and interests. When studied empirically, however, its properties are often reduced to the sum of the traits and attitudes of the individuals or groups that are populating it. This book shows how to move from an 'aggregative' to a relational view of civil society. Drawing upon field work on citizens' organizations in two British cities, this book combines network analysis and social movement theories to show how to represent civil society as a system of relations between multiple actors. 'Modes of coordination' enables us to identify different logics of collective action within the same local settings. The book exposes the weakness of rigid dichotomies, separating the voluntary sector from social movements, 'civic' activism oriented to service delivery from 'un-civic' protest, grassroots activism external to institutions from formal, professionalized organizations integrated within the 'system'
Literaturverz. S. 219 - 239
This book analyzes civil society as a field of organizations mobilizing on collective goals
Introduction: of King Solomon, Goethe, and civic networks; 1. Modes of coordination of collective action; 2. The importance of local comparisons: civic organizations in British cities; 3. Building civic networks: strategies of tie formation; 4. The structural bases of civil society; 5. Network positions and their incumbents; 6. The duality of organizations and events; 7. Network centrality and leadership; 8. Civic networks and urban governance; 9. 'Networking' contentious politics; Postfaction: bringing time and space(s) into the picture
Keywords: Netzwerk; Soziale Bewegung; Zivilgesellschaft